Strategi Pengelolaan Sampah Sistem Zero Waste Di Kelurahan Pegesangan Kota Mataram - Silmi, Hayatus; Zitri, Ilham (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2024)
This study aims to analyze the concept of zero waste, identify effective implementation strategies, assess the chances of success and establish an integrated waste management model for implementation in Pegesangan Village, Mataram City. This study uses descriptive and qualitative methods. The data sources for this study are primary data obtained directly from the government, private sector, universities, the community and information media. In addition, it is supported by secondary data obtained from documents, publications or literature related to zero waste system waste management strategies. The results of this study indicate that the lack of public awareness of the importance of waste management and the existence of traditional markets hinder the effectiveness of waste management and sorting, making it difficult to implement a zero-waste system in the Pegesangan Barat Village area. To overcome these obstacles, the Pegesangan Village Government implemented a "waste sorting" program between organic and inorganic waste. With proper waste separation, organic waste can be processed into useful compost and inorganic waste can be recycled or managed more efficiently. Therefore, community and government involvement is needed to create a waste management plan with a zero waste system, protect the environment, and produce benefits and economic value from the waste produced.